Climate Security and Policy Options in Japan - Hasui, Seiichiro (2021)
Climate security has been discussed in both academia and policy documents in the West. A key point that surfaces from these discussions is that the cooperation of non-military organizations is essential for effective responses to climate change-related threats. This overlaps considerably with debates on security in Japan, where the use of force is constitutionally restricted. Therefore, it is possible to localize the concept of climate security to the genealogy of Japan’s security policy that, in the 1980s and 1990s, sought a non-traditional security strategy that did not rely solely on military power in the name of “comprehensive security,” “environmental security,” and “human security.” In Japan, the perspective of climate security is rare. However, the introduction of a unique climate security concept into security policy enables the maintenance of national security and environmental conservation. Additionally, struggling with climate change alongside neighboring countries contributes to mutual confidence building and stability in international relations in Northeast Asia. To achieve this objective, we first show that climate security includes many kinds of security concerns by surveying previous studies and comparing Western countries’ climate security policies. Second, we follow the evolution of Japan’s security policy from 1980 to 2021. Finally, we review Japanese climate security policies and propose policy options.